1997
DOI: 10.1056/nejm199707033370101
|View full text |Cite
|
Sign up to set email alerts
|

Residential Exposure to Magnetic Fields and Acute Lymphoblastic Leukemia in Children

Abstract: Our results provide little evidence that living in homes characterized by high measured time-weighted average magnetic-field levels or by the highest wire-code category increases the risk of ALL in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
280
2
10

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 384 publications
(300 citation statements)
references
References 23 publications
7
280
2
10
Order By: Relevance
“…The percent agreement for W-L wire codes was 89%, and the k-statistic was 0.83 (95% CI ¼ 0.77-0.89), which were very similar to the 92% agreement and k-statistic of 0.89 (95% CI ¼ 0.84-0.94) found in the NCI childhood leukemia study (Linet et al, 1997;Tarone et al, 1998). The percent agreement for K-S wire codes was 95%, and the k-statistic ¼ 0.91 (95% CI 0.86-0.95), also very close to the results of the NCI childhood leukemia study, which reported 95% agreement and kstatistic of 0.93 (95% CI 0.88-0.97) (Linet et al, 1997;Tarone et al, 1998). The wire mappers selected for EBCLIS had no prior wire coding experience, unlike the NCI study, which had one wire mapper with substantial experience, P-values for testing differences between proportions of homes built prior to 1950, single family residences, W-L wire codes and K-S wire codes by region are for the Pearson w 2 test or Fisher's exact test.…”
Section: Reproducibilitysupporting
confidence: 76%
See 4 more Smart Citations
“…The percent agreement for W-L wire codes was 89%, and the k-statistic was 0.83 (95% CI ¼ 0.77-0.89), which were very similar to the 92% agreement and k-statistic of 0.89 (95% CI ¼ 0.84-0.94) found in the NCI childhood leukemia study (Linet et al, 1997;Tarone et al, 1998). The percent agreement for K-S wire codes was 95%, and the k-statistic ¼ 0.91 (95% CI 0.86-0.95), also very close to the results of the NCI childhood leukemia study, which reported 95% agreement and kstatistic of 0.93 (95% CI 0.88-0.97) (Linet et al, 1997;Tarone et al, 1998). The wire mappers selected for EBCLIS had no prior wire coding experience, unlike the NCI study, which had one wire mapper with substantial experience, P-values for testing differences between proportions of homes built prior to 1950, single family residences, W-L wire codes and K-S wire codes by region are for the Pearson w 2 test or Fisher's exact test.…”
Section: Reproducibilitysupporting
confidence: 76%
“…c EPEFcomposite estimated personal exposure measure=model that includes the mean 24-h broadband measurements in the bedroom and most lived-in room and the test-load coefficient in the most lived-in room. and one without (Linet et al, 1997;Tarone et al, 1998). However, the agreement between EBCLIS mappers was very good.…”
Section: Reproducibilitymentioning
confidence: 85%
See 3 more Smart Citations